Тусовки 6 "Б": повесть / Людмила Матвеева - Матвеева Людмила Григорьевна (Астрель, 2010)
Экземпляры: ф.14 (20180907) / Инвентарный номер: 55910 / Цена: 50.00 / Авт.знак: М 33 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6